Lifting of a Jeffrey fluid on a vertical belt under the simultaneous effects of magnetic field and wall slip conditions - Farooq, A. A.; Batiha, Belal; Siddiqui, A. M. (International Journal of Engineering and Technology, 2017)
Magnetohydrodynamic (MHD) thin film flow of an electrically conducting Jeffrey fluid over a vertically moving belt is investigated when a slippage between the surface and the fluid occurs. Exact expression for velocity profile is obtained and is displayed graphically to illustrate the effects of interesting flow parameters. Expressions for some important physical quantities such as volume flux, average velocity and the belt speed for the lifting of the Jeffrey fluid are also derived.